Performance Optimization of the Helical Heat Exchanger With Turbulator - Xifeng, Wang; Xiaoluan, Zhang; Mahariq, Ibrahim; Salem, Mohamed; Ghalandari, Mohammad; Ghadak, Farhad; Abedini, Mostafa (Frontiers in Energy Research, 2022)
In this paper, optimization on a two-tube helical heat exchanger with a fin is represented. The spiral pipes heat exchanger which is made of the cooper is adopted for investigation. The effects of three types of fins with the proposed geometric shapes on the overall heat transfer coefficient and pressure loss are investigated. The fins are located on the inner surface of the outer pipe. The obtained numerical results are compared with the experimental results, and a good agreement is observed between the results. The studies show that the total heat transfer coefficient has increased by 170% compared to an exchanger with no fin. Therefore, the best fin has been selected based on the benefit-cost-ratio (BCR) factor. Finally, using the new represented optimization algorithm, the height of the represented triangular fin is optimized to represent the best values for overall heat transfer coefficient and pressure loss of the helical heat exchanger. In addition, the results indicate that reducing the density and height of the triangular fin increases heat transfer and reduces pressure loss.